Direito ambiental: a educa????o ambiental como garantia instrumental do desenvolvimento sustent??vel - Ayoub, Riod Barbosa (2016)
The Environmental Education and Sustainable Development Instrumental Guarantee is subject of the current and through this research demonstrate how this formidable means of critical awareness makes individuals giving them the notion of the exact need to preserve nature-practicing development with ecological responsibility to provide quality life for everyone on our planet. The timing is critical , international organizations as well as all nations are constantly in meetings discussing solutions to combat environmental imbalance present, seeking alternatives to avoid the collapse of our ecosystems culminating in very serious consequences as the extinction of human life and other species. In this work, demonstrated adopted principles and measures can lead us to an equalization of how we should act to ensure the continuity of life over time.